2022
DOI: 10.3389/fimmu.2022.847861
|View full text |Cite
|
Sign up to set email alerts
|

Allicin Improves Intestinal Epithelial Barrier Function and Prevents LPS-Induced Barrier Damages of Intestinal Epithelial Cell Monolayers

Abstract: Gut barrier disruption is the initial pathogenesis of various diseases. We previously reported that dietary allicin improves tight junction proteins in the endoplasmic reticulum stressed jejunum. However, whether the allicin benefits the gut barrier within mycotoxin or endotoxin exposure is unknown. In the present study, IPEC-J2 cell monolayers within or without deoxynivalenol (DON) or lipopolysaccharide (LPS) challenges were employed to investigate the effects of allicin on intestinal barrier function and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition to against bacteria, allicin has also been shown to modulate the composition of gut microbiota (GM) and increase the diversity of beneficial bacteria in animal models ( Guillamón et al, 2021 ). Allicin has been found to play a role in improving intestinal epithelial barrier function and preventing barrier damage via a microbiota-regulated short-chain fatty acid-TLR4/MyD88/NF-κB cascade response in an acrylamide-induced rat model ( Yuan et al, 2021 ; Gao et al, 2022 ). Researchers suggested that allicin could block intestinal bacterial translocation by increasing the immunologic barrier function of mesenteric lymph nodes by modulating dendritic cell maturation ( Zhang Y. et al, 2017 ).…”
Section: Allicinmentioning
confidence: 99%
“…In addition to against bacteria, allicin has also been shown to modulate the composition of gut microbiota (GM) and increase the diversity of beneficial bacteria in animal models ( Guillamón et al, 2021 ). Allicin has been found to play a role in improving intestinal epithelial barrier function and preventing barrier damage via a microbiota-regulated short-chain fatty acid-TLR4/MyD88/NF-κB cascade response in an acrylamide-induced rat model ( Yuan et al, 2021 ; Gao et al, 2022 ). Researchers suggested that allicin could block intestinal bacterial translocation by increasing the immunologic barrier function of mesenteric lymph nodes by modulating dendritic cell maturation ( Zhang Y. et al, 2017 ).…”
Section: Allicinmentioning
confidence: 99%
“…Previous research has shown that LPS lowers expression of TJ proteins, which affects the intestinal barrier . LPS inhibited the IPEC-J2 cell monolayer model’s protein expression of ZO-1and claudin-1 . SC06 has the potential to reverse the LPS-induced downregulation of TJ protein expression.…”
Section: Discussionmentioning
confidence: 90%
“…42 LPS inhibited the IPEC-J2 cell monolayer model's protein expression of ZO-1and claudin-1. 43 SC06 has the potential to reverse the LPS-induced downregulation of TJ protein expression. In addition, weaned pigs treated with B. amyloliquefaciens showed an increase in the mucosal expression of TJ proteins in the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a sensitive biomarker of barrier strength and intestinal permeability [ 28 , 29 ]. LPS crosses the intestinal barrier into the bloodstream after intestinal damage and disperses throughout the body.…”
Section: Resultsmentioning
confidence: 99%